Evaluation of Physiotherapy Facilities and Infrastructure in the Medical Rehabilitation Unit of Grandmed Lubuk Pakam Hospital - Darmantoo Ginting (Medistra Medical Journal (MMJ), 2025)
Medical rehabilitation services, especially physiotherapy, play an important role in the process of restoring the function of movement and mobility of patients who experience disorders due to disease, injury or disability. The implementation of this service requires the availability of adequate facilities and infrastructure according to the standards set by the Ministry of Health of the Republic of Indonesia. This study aims to evaluate the condition of physiotherapy facilities and infrastructure in the Medical Rehabilitation Unit of Grandmed Lubuk Pakam Hospital . The method used was descriptive evaluative approach, with data obtained through direct observation, evaluation checklist, and interviews with physiotherapy staff and head of the unit. The results showed that about 70% of physiotherapy facilities were available and in good condition, but there were still important tools such as shoulder wheels and standing frames that were not yet available. In terms of infrastructure, the service space is adequate, but not yet fully disability-friendly, such as the unavailability of special toilets and access for patients with